1998
DOI: 10.1046/j.1365-2044.1998.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced hypothermia in the postoperative management of refractory cardiac failure following paediatric cardiac surgery

Abstract: Postoperative low cardiac output states are a major cause of postoperative mortality in infants and children following corrective cardiac surgery for congenital heart defects. In this unit, whole body hypothermia has been used since 1979 in the management of these low output states when they are refractory to conventional modes of therapy. Twenty cases treated in this way between July 1986 and June 1990 were reviewed in 1992. The current report reviews the 50 further cases treated with moderate hypothermia bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The fact that hypothermia can indeed improve circulatory parameters is shown by its successful usage in five small studies (three in pediatric patients and two in adults) to improve circulation and reverse refractory cardiac shock following cardiac surgery (87)(88)(89)(90)(91). Two small studies have reported that hypothermia can be used safely and effectively in hemodynamically unstable patients who remain comatose following cardiac arrest (166,167).…”
Section: Side Effects Of Induced Hypothermiamentioning
confidence: 99%
“…The fact that hypothermia can indeed improve circulatory parameters is shown by its successful usage in five small studies (three in pediatric patients and two in adults) to improve circulation and reverse refractory cardiac shock following cardiac surgery (87)(88)(89)(90)(91). Two small studies have reported that hypothermia can be used safely and effectively in hemodynamically unstable patients who remain comatose following cardiac arrest (166,167).…”
Section: Side Effects Of Induced Hypothermiamentioning
confidence: 99%
“…Following cardiac surgery, a persisting low cardiac output state refractory to conventional treatment is associated with a high mortality rate. The use of IH in this setting has been the subject of three reports (113)(114)(115). Deakin et al (113) reported the use of IH in 50 patients, and (from the same center) Dalrymple-Hay et al (114) reported the use of IH in 57 patients with cardiogenic shock following cardiac surgery.…”
Section: Clinical Applications Of Ihmentioning
confidence: 99%
“…Dalrymple-Hay and coworkers, 17 in a population of infants and children with congenital heart disease undergoing corrective cardiac surgery, reported the use of IH in 57 patients with cardiogenic shock following cardiac surgery; 54% had benefits in hemodynamic parameters and mortality. Single-institution experiences by Moat and coworkers 18 and Deakin and coworkers 19 have reported comparable survival results in smaller pediatric populations. This case appears to be the first report describing a heart transplant patient who was successfully resuscitated and treated with therapeutic hypothermia prior to surgical placement of a left ventricular assist device.…”
Section: Discussionmentioning
confidence: 92%
“…13 The cardioprotective effects of IH have been applied in adult and pediatric cardiac surgery patients to manage refractory cardiogenic shock; to date, 5 case series have reported on the use of IH in patients with refractory cardiogenic shock following cardiac surgery. [15][16][17][18][19] Yahagi and coworkers 15 found that in 10 adult patients with cardiogenic shock following cardiac surgery, despite the use of intra-aortic balloon pumps (IABPs) and catecholamines, they were more successful in weaning patients from IABPs with the use of IH. Moriyama and coworkers 16 reviewed cardiac hemodynamics in 8 adult postcardiotomy ventricular failure patients and found significant improvements in tissue oxygen consumption through varying durations of hypothermia.…”
Section: Discussionmentioning
confidence: 99%